E-learning in Mongolian Higher Education - Suvdmaa Tuul (Athabasca University Press, 2016)
This paper reviews the e-learning course development in selected universities of Mongolia and attempts to classify the e-learning programs that are in practice at the tertiary education level in the country. The given paper uses both secondary and primary sources.